Biocontrol of wilt disease of rice seedlings incited by Fusarium oxysporum through soil application of Streptomyces chilikensis RC1830. (31st August 2022) - Behera, H.T.; Mojumdar, A.; Behera, S.S.; Das, S.; Ray, L.
Abstract: The genus Streptomyces includes many antifungal metabolite‐producing novel strains. Fusarium oxysporum soil‐inhabiting pathogenic fungi, that affects rice to cause wilt disease. This work demonstrates the efficacy of novel Streptomyces chilikensis strain RC1830, previously isolated from estuarine habitat Chilika Lake in preventing the F. oxysporum wilting/root rot disease and promoting the growth of rice (Var. Swarna) seedlings. A total of 25 different compounds were identified from crude extracts of S. chilikensis RC1830 by GC–MS. In pot trial experiments, Streptomyces ‐treated rice seedlings showed significantly reduced disease severity index by 80·51%. The seedlings growth parameters (root length, root fresh weight and root dry weight) were also increased by 53·91, 62·5 and 73·46%, respectively, in Streptomyces ‐treated groups of seedlings compared to Fusarium‐ infected seedlings. Similarly, the shoot length, shoot dry weight and shoot fresh weight were also increased by 26, 58 and 34·4%, respectively, in Streptomyces ‐treated groups of seedlings compared to Fusarium‐ infected seedlings. Formulations of the strain were prepared using seven organic and inorganic wastes as the carrier material and the shelf lives of the propagules were also monitored. Vermiculite and activated charcoal formulations stored at 4°C exhibited a higher viable cell count after 3 months of storage. Abstract : Significance and Impact of the Study: This study focuses on the antifungal activity of novel Streptomyces chilikensis RC1830 and its application in the biocontrol of wilt diseases of rice seedlings by Fusarium oxysporum through soil application. Application of microbial cultures directly onto the agricultural sector as a biofertilizer is not so beneficial, so the strain RC1830 were formulated with several carrier materials for the production of portable and convenient form. The strain could be a potential development strategy as biofertilizer for economically important crops. A new whole‐cell microbe‐based bioformulation for plant growth promotion with antifungal properties was formulated with a shelf life of 3 months.